Dental and Oral Health Promotion Video Media on the Knowledge of Prolanis Patients - Robbihi, Hilmiy Ila; Kristiani, Anie; Widiyagdo, Agung (Journal Center of Excellent : Health Assistive Technology, 2024)
Dental and oral health is a top priority for everyone, including prolanis patients. Prolanis is a proactive and integrated chronic disease management program involving participants, health facilities, especially community health centers and BPJS Health, aimed at encouraging chronic disease patients to achieve optimal quality of life services, one of which is dental and oral health. Education about dental and oral health needs to be provided to prolanis patients. This education needs to use media so that targets can more quickly understand the education provided, such as video and non-video media (flipcharts). The aim of this research is to analyze changes in knowledge before and after being given counseling using video media to prolanis patients, in the work area of the Mangkubumi Health Center, Tasikmalaya City in 2023. This research method uses a quantitative approach with a Quasi-Experimental research type with a Two Group Pretest and Posttest Design. Based on the results of statistical knowledge tests in the experimental group and control group, it was found that there was no significant difference between the results of dental and oral health knowledge before and after being given intervention using video and non-video with a significance value of 0.910, meaning p > 0.05. The results of the Mann-Whitney statistical test showed that the knowledge of the experimental group was an average of 20.30 and the control group had an average of 20.70. p=value of 0.910 is greater than the significance level of p > 0.05. This means that there is no significant difference between the results of dental and oral health knowledge using video and non-video. In conclusion, it was found that flipcharts were more effective than videos in increasing dental and oral health knowledge in Prolanis with a difference of 0.5 more effective in increasing flipchart media.